Wavelength-Tuneable Near-Infrared Luminescence in Mixed Tin–Lead Halide Perovskites - Liu, Meiyue; Zhao, Ru; Sun, Fuhao; Zhang, Putao; Zhang, Rui; Chen, Zeng; Li, Shengjun (Frontiers in Chemistry, 2022)
Near-infrared light-emitting diodes (NIR-LEDs) are widely used in various applications, such as night-vision devices, optical communication, biological imaging and optical diagnosis. Solution-processed high-efficiency perovskite NIR-LEDs are mostly based on CsPbI3 and FAPbI3 with emission peaks at 700-800 nm which limits their NIR applications. NIR-LEDs with longer emission wavelengths near 900 nm can be obtained by replacing lead with tin. However, Sn-based perovskite LEDs exhibited low efficiency due to the high concentration of Sn-related defects and Sn2+ easily oxidizes to Sn4+, which leads to device degradation. This issue can be solved by partially replacing lead with tin. Mixed Sn-Pb halide perovskites with a smaller bandgap and superior stability compared to pure Sn-based perovskites are promising candidates. In this study, we systematically investigated the optical properties of a broad family of hybrid Sn and Pb iodide compounds with methylammonium, formamidinium and caesium cations stabilised in a 3D perovskite structure. The emission spectra of the mixed Sn-Pb halide perovskites were tuned by changing the Sn:Pb ratio the peak emission wavelength ranged from 710 nm to slightly longer than 950 nm. A comparison of the absorption and photoluminescence emission properties of the compositions confirmed that the MA-based and FA-based mixed Sn-Pb halide perovskites are promising for the manufacture of low-cost, efficient NIR-LEDs.